The soul of the Greeks : an inquiry - Davis, Michael (Chicago : University of Chicago Press, 2011)
Analyzes works by Homer, Herodotus, Euripides, Plato, and Aristotle to reveal how the ancient Greeks portrayed and understood what the author calls 'the fully human soul'. Beginning with Homer's "Iliad", this work lays out the tension within the soul of Achilles between immortality and life.
The soul of Achilles -- Aristotle -- The doubleness of soul -- Out of itself for the sake of itself -- Nutritive soul -- Sensing soul: vision -- Thinking soul. Sensation and imagination -- Passive and active mind -- Imagination and thought -- The soul as self and self-aware -- "The father of the Logos" -- "For the friend is another self" -- Herodotus: the rest and motion of soul -- Rest in motion: Herodotus's Egypt -- Motion at rest: Herodotus's Scythians -- Euripides: soul as same and other -- The fake that launched a thousand ships: the duplicity of identity in the Helen -- Euripides among the Athenians: the double vision of soul in Iphigeneia among the Taurians -- Plato -- The soul of the law: Gyges in Herodotus and in Plato -- The subject of justice: on Plato's Cleitophon -- The object of tyranny: Plato's Hipparchus -- Plato's Phaedrus: Er's and the structure of soul -- The grammar of soul: the middle voice in Plato's Euthyphro -- The soul of Socrates.
Keywords: Greek literature -- History and criticism; Philosophy, Ancient; Soul in literature; Soul; antiikin filosofia; sielu; Kreikka